Tackling antimicrobial resistance through education. Issue 9 (5th May 2015) - Jethwa, Shilpa
<x xml:space="preserve">Abstract</x> Improving understanding of antimicrobial use can help curb inappropriate prescribing and consequently antimicrobial resistance. All levels of healthcare must join forces to combat this problem.